1980
DOI: 10.1677/joe.0.0840163
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Significance of Androgen-Induced Ovulation in the Hen

Abstract: The ovulation-inducing property of androgens in the laying hen was investigated. In a first experiment, four different androgens were injected subcutaneously into single-comb White Leghorn hens on the day of the last oviposition of a sequence. The hens were killed 10 h later and examined for the presence of an ovum in the oviduct. Testosterone induced ovulation in accordance to the dose injected (median effective dose, 966 +/- 193 microgram/hen) but the responses to 5 alpha-dihydrotestosterone and 5 alpha-andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…In the absence of more information on the dose effectiveness and metabolic activity of cyproterone acetate in the hen, the possibility that the drug took several days to build up an adequate receptor block cannot be excluded. However, the loss of lay took as long to Croze & Etches (1980), possibly through the conversion of the hormone to an active metabolite such as 4-androstene-3,17-dione (Davies, Massa & James, 1980;Croze & Etches, 1980). (Gilbert, 1971), it is unlikely that the ovary is an androgen target organ (although the possibility of dependence on adrenal androgen cannot be excluded).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of more information on the dose effectiveness and metabolic activity of cyproterone acetate in the hen, the possibility that the drug took several days to build up an adequate receptor block cannot be excluded. However, the loss of lay took as long to Croze & Etches (1980), possibly through the conversion of the hormone to an active metabolite such as 4-androstene-3,17-dione (Davies, Massa & James, 1980;Croze & Etches, 1980). (Gilbert, 1971), it is unlikely that the ovary is an androgen target organ (although the possibility of dependence on adrenal androgen cannot be excluded).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to establish the nature of this feedback stimulus have shown that several steroids are able to release LH and cause ovulation when injected into hens. Testosterone and progesterone have been considered to be the most likely steroids involved because they are effective exogenously (Wilson & Sharp, 1975Etches & Cunningham, 1976; Croze & Etches, 1980), and also show patterns of endogenous release which would be consistent with such a role (Furr, Bonney, England & Cunningham, 1973;Shodono, Nakamura, Tanabe & Wakabayashi, 1975;Etches & Cunningham, 1977). Etches & Cunningham (1977) found that an increase in plasma LH concentration was always preceded by an increase in testosterone concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovarian source of the pre-ovulatory surge of progesterone is primarily the granulosa cell layer of the mature pre-ovulatory follicle (F1), while the pre-ovulatory release of testosterone originates from all hierarchical pre-ovulatory follicles (Etches & Duke 1984). Injection of testosterone can induce ovulation associated with a pre-ovulatory release of progesterone, but only if the injection results in unphysiologically high concentrations of circulating testosterone (Croze & Etches 1980). Because passive immunization with testosterone antibodies blocks spontaneous ovulation (Furr & Smith 1975) and the preovulatory release of testosterone is initiated before that of progesterone (Etches & Cunningham 1977, Williams & Sharp 1978, Wilson & Cunningham 1984, it has been suggested that the pre-ovulatory release of testosterone may act to prime the hypothalamo-pituitary axis to facilitate the pre-ovulatory release of LH (Croze & Etches 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Injection of testosterone can induce ovulation associated with a pre-ovulatory release of progesterone, but only if the injection results in unphysiologically high concentrations of circulating testosterone (Croze & Etches 1980). Because passive immunization with testosterone antibodies blocks spontaneous ovulation (Furr & Smith 1975) and the preovulatory release of testosterone is initiated before that of progesterone (Etches & Cunningham 1977, Williams & Sharp 1978, Wilson & Cunningham 1984, it has been suggested that the pre-ovulatory release of testosterone may act to prime the hypothalamo-pituitary axis to facilitate the pre-ovulatory release of LH (Croze & Etches 1980). We have shown that active or passive immunization of laying hens against testosterone blocks ovulation without affecting the development of hierarchical preovulatory follicles (Rangel et al 2005), and that treatment of laying hens with flutamide, a testosterone antagonist, blocks the pre-ovulatory surges of both progesterone and LH and ovulation (Rangel et al 2006).…”
Section: Introductionmentioning
confidence: 99%